Using Calming Beds to Reduce PANNS-EC Scores in Patients with Violent Behaviors - Dwidiyanti, Meidiana; Kandar, Kandar; Suerni, Titik; Wimala, Dina; Wijayanti, Diyan Yuli (Universitas Aisyah Pringsewu, 2022)
Background: Patients with violent behaviors have the potential to harm themselves, others, and their environment. The management of patients with violent behavior needs to consider various aspects, one of which is patients’ spiritual aspect. Combining a spiritual therapy of listening to Qur’an recitation, acupressure, and using a new innovation of a calming bed during the intervention is expected to increase the effect of relaxation and patients’ comfort to optimize the intervention outcomes, namely to reduce aggression level in patients with violent behaviors. Objective: This study aimed to determine the effect of the combined intervention of listening to Qur’an recitation (murottal), acupressure, and using a calming bed on reducing the Positive and Negative Syndrome Scale - Excited Component (PANSS-EC) scores in patients with violent behaviors. Methods: This study used a pre-post test quasi-experimental design without a control group. A total of 50 respondents who agreed to participate in the therapy entirely were randomly recruited. The therapy was given four times with a duration of 30 minutes each. The paired t-test was performed to find out the effect of the intervention. Results: The results showed a significant effect of the intervention on reducing the PANSS-EC score among patients with violent behavior (p=0.000). Conclusion: The combination intervention of listening to Qur’an recitation, acupressure, and use of calming beds can reduce symptoms of violent behaviors by decreasing the PANSS-EC scores. This study suggests using spiritual intervention to help patients with violent behaviors reduce their aggression. Abstrak: Latar Belakang: Pasien dengan perilaku kekerasan berpotensi membahayakan diri sendiri, orang lain, dan lingkungannya. Penanganan pasien dengan perilaku kekerasan harus memperhatikan berbagai aspek, salah satunya adalah aspek spiritual. Kombinasi terapi spiritual dengan mendengarkan murrotal dan acupressure, serta inovasi terbaru penggunaan calming bed selama pemberian intervensi diharapkan mampu meningkatkan efek relaksasi dan kenyamanan pasien sehingga dapat mengoptimalkan hasil intervensi yang diberikan yaitu untuk menurunkan tingkat agresi pada pasien dengan perilaku kekerasan. Tujuan: Penelitian ini bertujuan untuk mengetahui efektivitas intervensi kombinasi antara mendengarkan murottal dan acupressure serta penggunaan calming bed dalam menurunkan PANSS-EC skor. Metode: Penelitian ini merupakan penelitian dengan pre dan post-test intervensi tanpa kelompok kontrol. Sampling yang digunakan adalah randomized control trial dengan 50 responden yang bersedia mengikuti terapi dari awal sampai akhir. Terapi diberikan sebanyak 4 kali dengan durasi 30 menit per intervensi. Analisis yang digunakan adalah paired t-test untuk mengetahui pengaruh intervensi. Hasil: Hasil penelitian menunjukkan adanya pengaruh yang signifikan dari pemberian intervensi spiritual kolaborasi dengan acupressure dan calming bed terhadap penurunan perilaku kekerasan dilihat dari skor PANSS-EC (p=0,000). Kesimpulan: Intervensi kolaborasi yang diberikan dapat menurunkan gejala perilaku kekerasan dengan penurunan skor PANSS-EC sesudah intervensi. Dalam pelayanan kesehatan disarankan adanya terapi spiritual dalam membantu menurunkan tingkat agresi pada pasien.